BEHIND THE MEDIA IN AMERICA: NEWS COVERAGE AND MEDIA BIAS; AS REFLECTED IN NIGHTCRAWLER - Mulkiana, Adhe Rizki (LANTERN (Journal on English Language, Culture and Literature), 2016)
Nightcrawler is a movie which is written and directed by Don Gilroy shows how media works. This movie tells about a freelancer cameraman named Louis Bloom who looks for footage of a news, records it and sell it to a news station. The aims of this thesis are to describe the intrinsic and extrinsic aspects of the movie. The intrinsic aspects cover the narrative elements (theme, characters, setting, plot and conflict) and cinematic elements (camera distance, mise-en-scene and sound) while the extrinsic aspects cover how media works based on agenda setting theory, the news coverage and media bias in Nightcrawler. The writer used library research to support the data analysis obtained from some references, such as some related books, journals and articles. The result of this thesis is in the process of how the news produced, there are some modifications of information so the news will be more suitable with the value of where the company comes from. The process itself contains some editing process of how media covers an issue, which can lead into media bias.